SISTEM PERTANIAN TERPADU YANG MENINGKATKAN PRODUKTIVITAS PERTANIAN DI LAHAN PEKARANGAN - Ihsan R.A. Saibi; Silvia, Silvia Permata Sari; Aries Kusumawati (Jurnal Pertanian Agros, 2025)
Integrated Farming System is a modern agriculture that has a sustainable and environmentally friendly concept with productivity as a result. The utilization of yard land not only increases agricultural productivity but in economic terms can also increase socio-economic needs with good management. The benefits obtained by applying this principle are that the cost of shopping for food and vegetable needs can be reduced, and daily spice ingredients can be met. The purpose of writing this study is to find out and analyze how agricultural productivity in Indonesia is by utilizing yard land in residential homes and cities. The utilization of yard land to increase agricultural productivity has proven to be influential. The utilization of yard land that is managed properly will get great benefits, can preserve the environment, and minimize the use of inorganic materials. The utilization of this yard land has many benefits for the surrounding community both in terms of agricultural productivity and in terms of economy. The utilization of yard land can be done in various ways, starting from hydroponic cultivation techniques, aquaponics, vertical culture (hanging, attached, pot, or polybag systems).